STRATEGI KOMUNIKASI KOMISI PENYIARAN INDONESIA (KPI) ACEH DALAM MENGOPTIMALISASI MIGRASI TELEVISI DIGITAL - Zuwidah Dewi; Muzakkir Muzakkir (JIMSI: Jurnal Ilmiah Mahasiswa Ilmu Komunikasi, 2022)
The transition from analog television broadcasting to digital is a form of carrying out the mandate of Article 60 A of Law Number 32 of 2002 concerning broadcasting, which as has been changed to Law Number 11 of 2020 concerning work copyright. This study aims to analyze the communication strategy used by the Indonesian Broadcasting Commission (KPI) Aceh in the program to switch television broadcasts from analog to digital. Technological progress is felt today, therefore it is necessary to have the right communication strategy, especially in the development of broadcasting technology. This study uses Lasswell's communication model theory in the process, with this study using a qualitative descriptive method. Data collection techniques through interviews, observations and additional data as a complement.Indonesian Broadcasting Commission (KPI) Aceh as the object of research. The results of this study explain, the role of KPI Aceh in the digital television migration project is an effort to socialize. Until now, socialization has been carried out directly, online or through internet media. The right socialization strategy will have a good impact on the progress of the nation.